Slovenian attitude to the war in Ukraine - Lovec, Marko (Teorija in praksa, 2025)
The purpose of this article is to explain the position held by Slovenia with respect to the war in Ukraine. The article draws on literature that stresses the importance of supply-side ideologies in explaining variations beyond the role of the international system, notably populism, Euroscepticism, radical ideologies and government–opposition dynamics, as opposed to demand-side attitudes and policy implications. Among post-socialist small countries, the stronger role of anti-systemic and anti-establishment actors and attitudes, together with the potentially stronger negative effects of war, make differences in positions more likely. Empirical study of the f irst 2 years of the war shows that the ideologies of the actors play a key role in explaining attitudes. Populist, Eurosceptic and far-right actors tend to be more pro-Russian, while differences exist among left-wing actors. However, anti-establishment sentiment mainly affected the dynamics between government and opposition, whereas the electoral performance of anti-system actors remained low, as can be explained by the still relatively pro-system attitude of the public and the war’s limited impact.
Keywords: ideologija; ideology; javno mnenje; political parties; politične stranke; public opinion; Slovenia; Slovenija; Ukraine war; vojna v Ukrajini